THE INFLUENCE OF PSYCHO-PHYSIOLOGICAL CHARACTERISTICS OF DRIVERS WITH UP-TO-THREE-YEAR EXPERIENCE OF DRIVING ON THEIRCOMMITTING TRAFFIC VIOLATIONS AND ACCIDENTS - E. M. Mukhin; A. M. Prokhorova; M. E. Spirin; V. A. Mazur; A. I. Fedorov (Вестник Кемеровского государственного университета, 2013)
The study of individual and typological characteristics of higher nervous activity and their significance in goaldirected behavior in varying degrees of exposure opens the way to understanding the biological basis of individual differences between people, deciphering the neurophysiological mechanisms of complex psychological phenomena. Without knowing the real bases of individual psycho-physiological differences one can not really implement practical human activity man.